The High Motivation of Indonesian Migrant Worker Candidates and Its Implications for Educational Financing - Suhaidir; Marwazi; Siti Raudhatul Jannah (Yayasan Azhar Amanaa Yogyakarta, 2025)
This study examines the role of government policies in supporting and protecting Indonesian migrant workers from Kerinci Regency. With approximately 14,836 migrant workers from Kerinci working abroad in 2024, the need for policies that address their rights, safety, and welfare is increasingly crucial. Through qualitative analysis, this research explores the impact of government initiatives such as pre-departure training, legal assistance, secure remittance channels, and family support programs. These policies, facilitated by the Indonesian Migrant Workers Protection Agency (BP2MI) and local authorities, are analyzed through the lenses of Human Capital Theory, Legal Realism, and Adaptive Management Theory. Findings indicate that these policies significantly enhance the security and well-being of migrant workers, enabling them to achieve financial stability and contribute to community development. This study highlights the importance of continuous policy adaptation to meet the evolving needs of migrant workers, ultimately supporting both individual success and regional growth.